Geocaching: tracing geotagged social media research using mixed methods - Varga, Judit (2021)
This thesis explores the development of academic research with geotagged social media data (geosocial research) - an emerging computational, digital social research field - using 19 semi-structured interviews with scholars from diverse disciplines, participant observation at a geosocial research summer school and scientometrics. It asks: 'how can we study the development of geosocial research approaches through combining STS and scientometrics?' for five main reasons: to explore the diversity of computational social research; reflect on the ESRC's (2013) call to 'close the gap' between quantitative and qualitative human geography; contribute to methodological discussions in academic literature which call for combining STS and scientometrics; co-compose knowledge with distinct ways of knowing through mixing methods; and inform research methods curriculum development in the social sciences.